Two steps backwards: A bibliometric analysis of L2 vocabulary research in 1984 - Paul Meara (LingBaW, 2016)
This paper is the fourth instalment in a series of studies which attempt to plot the way research in L2 vocabulary acquisition has developed over the last fifty years. Earlier papers have analysed the research for 1982, 1983 and 2006 (Meara 2012, 2014, 2015). This paper follows on directly from my analysis of the 1983 research, and it uses the same bibliometric techniques that were used in the earlier papers: the co-citation methodology, first developed by Small (1973) and White and Griffith (1981). The analysis of the 1984 data shows some consolidation of the main research themes, but for the most part the L2 vocabulary research published in this year continues to be made up of small research clusters, sharing few common points of reference.